Design of a Scavenging Pyrrole Additive for High Voltage Lithium-Ion Batteries. Issue 4 (1st April 2022) - Yang, Jianzhong; Rodrigues, Marco-Tulio Fonseca; Yu, Zhou; Son, Seoung-Bum; Liu, Kewei; Dietz Rago, Nancy L; Cheng, Lei; Zhang, Zhengcheng; Abraham, Daniel; Liao, Chen
Abstract : We report 1-(dimethylamino) pyrrole (PyDMA) as an electrolyte additive for high voltage lithium-ion batteries based on LiNi0.6 Mn0.2 Co0.2 O2 (NMC622)//Graphite with an upper cutoff voltage of 4.4 V. Density Functional Theory (DFT) modeling indicates that the unique structure of PyDMA could be effective in preventing the hydrolysis of LiPF6 in a carbonate electrolyte, mitigating issues related to HF formation. The calculations also indicated that the additive would oxidize at lower potentials than typical electrolyte solvents, which could lead to protective films at the cathode surface. These expectations were tested using Nuclear Magnetic Resonance (NMR) and extensive electrochemical characterization. NMR studies confirmed the superb dehydrating capability of PyDMA, which successfully prevents HF formation even at high water content. Addition of 0.5 wt% PyDMA resulted in improved capacity retention in full-cells, and also in lower levels of transition metal dissolution from the cathode. Incremental capacity (dQ/dV) analysis indicates that benefits of PyDMA at low concentration (0.5–1 wt%) are associated with decreased rates of Li + -trapping reactions, and that higher concentrations of the additive can lead to isolation of cathode domains. Our study indicates that PyDMA could be a promising electrolyte additive for high voltage lithium-ion batteries at a low concentration.